Alternative Use of the Ilizarov Apparatus Set in Case of Complications During Intramedullary Nail Removal: A Case Report. Issue 2 (April 2021) - Malagoli, Emiliano; Kirienko, Alexander; Berlusconi, Marco Luigi Maria; Peschiera, Valeria; Lucchesi, Giovanni
Abstract : Case: We present 2 case reports: the first, a diaphyseal fracture of the humerus treated with a Marchetti nail resulting in a nonunion in 2017. The second, a fracture of the femur treated with a Kuntscher nail in 1989. A gunshot injury to that femur in 2014 evolved in nonunion and displacement. In both cases, the old nails were removed by using pieces of the Ilizarov apparatus. Conclusions: In case of complications, the versatility of the Ilizarov apparatus allows us to connect the intramedullary element to the universal extraction system; it proves itself to be an excellent cost-effective extraction system.